Men in Zero Point: Stamping out Drugs Double Epidemic and HIV-AIDS through Harm Reduction - Tri Cahyono, Sunit Agus; Udiati, Trilaksmi (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The main cause of drugs and HIV-Aids double epidemic in Indonesia is the change of using pattern from smoking to injection and the widespread of injection (IDU-Penasun) use among abusers, which in general having human capital weakness, or logical weakness, so they depend on drugs without awareness of its infectious contamination which threaten them. They are not aware that â€œgold bridgeâ€ of contamination and spread HIV-AIDS virus is not-sterilized injection needle use by turns. One of efforts to prevent HIV-AIDS virus contagion among injecting abusers is harm reduction (HR), in Indonesian terminology called the reduction of drugs bad effect. The main goal of this program is cutting contagious link of HIV-AIDS virus, from the main to special goal in Penasun community (injection use). In its implementation, HR program faces several handicaps, one of them is there has been yet a legitimating law conducting the program; sociology and religious handicaps related to Indonesia norm; budget and geographical handicaps because of the wide area and its outreach that need huge budget to implement the program; to anticipate those handicaps, the implementation of harm reduction needs good consideration to protect and safe people from double epidemic drugs and HIV-AIDS with still holding socio-culture, and Indonesian identity.